New perspectives on metagenomic analysis for pathogen monitoring in sustainable freshwater aquaculture production: a systematic review - Macedo, Daralyns Borges; dos Anjos, Thais Mayara Castro; De Los Santos, Edian Franklin Franco; Rodrigues, Marília Danyelle Nunes; Alegria, Oscar Victor Cardenas; Ramos, Rommel Thiago Jucá (Frontiers in Freshwater Science, 2024)
The freshwater and saltwater aquatic food sector has experienced the most significant growth in recent years and is increasingly recognized as a sustainable alternative for fostering prosperous societies selfsufficiently and ecologically. One primary economic and health risk factor in aquaculture production is health control, with potentially more severe impacts observed in tropical and developing countries. While metagenomics holds great promise for application in agro-industrial fields like aquaculture, its adoption remains limited. Consequently, this study aimed to assess the prospects for developing and applying metagenomics in identifying pathogens in freshwater aquaculture. The WIPO database was used to search for patents developed using metagenomics to monitoring pathogens in freshwater aquaculture. Metagenomics methods have been extensively employed in different fields, such as, medicine, veterinary, biotechnology, agriculture, particularly in studies focusing on microbial communities in different ecosystems. In aquaculture, the utilization of metagenomics has predominantly revolved around investigating antibiotic resistance genes, primarily in saltwater farms. Despite this, freshwater aquaculture, particularly in fish and crustacean farming, aligns closely with sustainable development goals, notably (SDGs) 2, 3, 6, and 13. Countries such as the United States of America, South Korea, and Canada stand at the forefront of utilizing metagenomics for disease monitoring in freshwater aquaculture, evidenced by their active patent developments. The PAGE \* Arabic \* MERGEFORMAT 3 metagenomic analysis, coupled with bioinformatics tools and databases, represents a rapid, secure, and non-invasive approach to environmental monitoring for preventive purposes.